Overview of Hearing Impairment in Barakat Syndrome - Habib Zalzal; Ibrahim Ibrahim; Amin J Barakat (Medical Science: Trends and Innovations Vol. 2, 2025)
Barakat syndrome, also known as HDR (Hypoparathyroidism, Deafness, Renal disease) syndrome, is a rare, clinically heterogeneous, genetic condition characterized by the triad of hypoparathyroidism, sensorineural hearing loss, and renal disease. It is most frequently associated with a mutation in the gene coding for the GATA3 transcription factor on chromosome 10p14. Hearing loss is the most prevalent manifestation of the syndrome, affecting 96% of reported cases. Universal newborn hearing screening has allowed for the early detection of sensorineural hearing loss, which is usually bilateral, ranges from mild to profound, and is more pronounced at higher frequencies. The GATA3 mutation has been found to alter the proper functioning of all cochlear cells, leading to hearing loss. The implementation of next-generation sequencing panels that include GATA3 in the workup of isolated hearing loss has allowed for early detection of the syndrome. Hearing treatment should be initiated as early as possible to allow for optimal speech, social skills, and language development. In this chapter, we discuss the characteristics, genetics, and management of the sensorineural hearing loss associated with Barakat syndrome.